(untitled) (Biological Sciences - PJSIR, 2022)
The electrical conductivities of complexes of some thiazolylazo-pyrimidine derivative complexes have been investigated at different temperatures. The complexes were found to be of two types; the first one has a semi-conductor behaviour and a constant conductivity value above 398°K, whereas the second type shows three segments with variable activation energy. The dissimilarity between the two types of complexes is attributed to the steric effect of the phenyl group in the first type. The conductivity data measured in the temperature range 298° - 5700K were correlated to the geometrical change of these complexes, indicating that the cobalt (II) complexes have higher conductivity than those of copper (1I) and nickel (II), depending on the chemistry of the metal ion and the molecular structure of complexes. Empirical equations to correlate E with log Go values for the complexes were deduced by the use of the least square method. Also, the mobility values (m) of these complexes were calculated.